2018
DOI: 10.1096/fasebj.2018.32.1_supplement.538.6
|View full text |Cite
|
Sign up to set email alerts
|

Role of GSTT1 and GSTM1 gene polymorphism for development of preeclampsia in Bangladeshi women

Abstract: Worldwide, pre‐eclampsia (PE) ranks as a major obstetric problem leading to substantial maternal and perinatal morbidity and mortality, especially in developing countries. Clinically it appears as a maternal syndrome, including hypertension and proteinuria after second half of pregnancy. PE affected by genetic trait, is associated with oxidative stress due to imbalance between the production of reactive oxygen species and the ability of antioxidant process. The glutathione S‐transferases (GST) are a group of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Although the risk of developing preeclampsia was higher for patients with the GSTT1 genotype, it was not significant [68]. However, the risk of developing preeclampsia with a combined GSTM1 and GSTT1 genotype was much higher relative to the GSTM1 null genotype alone [68]. These results are similar to another study in Mexican mestizo populations that demonstrated that patients with the combined GSTM1/GSTT1 deletion genotype conferred a marginally higher risk of preeclampsia versus the controls [67].…”
Section: Nitric Oxide Storage and Transport In Cells Are Mediated By ...supporting
confidence: 82%
See 2 more Smart Citations
“…Although the risk of developing preeclampsia was higher for patients with the GSTT1 genotype, it was not significant [68]. However, the risk of developing preeclampsia with a combined GSTM1 and GSTT1 genotype was much higher relative to the GSTM1 null genotype alone [68]. These results are similar to another study in Mexican mestizo populations that demonstrated that patients with the combined GSTM1/GSTT1 deletion genotype conferred a marginally higher risk of preeclampsia versus the controls [67].…”
Section: Nitric Oxide Storage and Transport In Cells Are Mediated By ...supporting
confidence: 82%
“…Consistent with the interaction of DNICs with GSTs, it is interesting to discuss studies demonstrating the association between the GSTM1 and GSTT1 null genotype and NO-related disorders, including preeclampsia, hypertension, and atherogenesis [65][66][67][68]. A 2018 study of 104 patients with preeclampsia and 200 healthy controls identified a highly significant (p < 0.001) association between the GSTM1 null genotype and the development of preeclampsia [68].…”
Section: Nitric Oxide Storage and Transport In Cells Are Mediated By ...mentioning
confidence: 91%
See 1 more Smart Citation
“…Further studies examining the GSTs and their roles in regulating vasodilation via its interactions with NO could lead to new therapeutic avenues to treat hypertension and other related disorders. In particular, the GSTM1 null genotype has been associated with an increased risk of blood pressure-related disorders such as preeclampsia and hypertension [ 71 , 72 , 73 , 74 , 75 ]. Investigations exploring the interaction of GSTM1 with NO, especially as DNICs, and the impact on sGC activation would provide novel insights for the treatment of these conditions and potentially advance the development of new vasodilators.…”
Section: Discussionmentioning
confidence: 99%